Hipokrisi Politik dalam Lanskap Kekuasaan di Indonesia Anomali dan Otokritik Demokrasi Digital - Achmad Fachrudin (Jaringan Pemberdayaan Politik Lingkungan Hidup, 2023)
Hypocrisy or political hypocrisy has a long history. In Indonesia, its roots can be stretched far back to the era of the archipelago kingdom, the period of colonialism and imperialism, the new order to the reform era. It is not uncommon for political hypocrisy to exist in conjunction with the emergence of feudalism, patrimonialism, nepotism, political dynasties, despotism, feudalism and so on, both systemically and in the practice of managing power. The presence of the era of liberal democracy which emerged at the same time as the post truth era, has made the issue of political hypocrisy in the landscape and stage of power in Indonesia increasingly complex and crucial, in addition to increasingly difficult and complex solutions or solutions. Likewise, efforts to realize digital democracy that can produce politicians with integrity are a necessity that must be carried out. For this reason, comprehensive and systematic digital democracy education and literacy steps are needed, especially during the 2024 Simultaneous Elections.